Production of Multiple Freshwater by Reverse Osmosis Seawater Desalination - Lu, Yanyue; Liao, Anping; Hu, Yangdong (Asian Journal of Chemistry, 2012)
An optimization method based on process synthesis has been presented and applied to design a reverse osmosis system. Multiple freshwater can be produced by the seawater desalination system using reverse osmosis membrane module. A simplified superstructure that contains all the feasible design for this desalination problem has been presented firstly. Then, membrane separation units employing the spiral wound reverse osmosis elements were described by using a pressure vessel model, which takes into account the pressure drop and concentration changes in the membrane channel. The optimum design problem can be formulated as a mixed-integer non-linear programming problem, which minimizes the total annualized cost of the reverse osmosis system. The effectiveness of this design methodology has been demonstrated by solving a desalination case.